Potensi Ekonomi Pemanfaatan Lahan Pekarangan di Desa Tambakrejo Kecamatan Jombang Kabupaten Jombang - Siswantoro, Rinto; Yuliana, Anggi Indah (Proceedings Series on Physical & Formal Sciences, 2021)
This study aims to 1) find out the form of yardland use 2) find out the amount of initial capital used in the utilization of yardland 3) find out how much the contribution of yardland use in addition to household economic income. This research was conducted in Tambakrejo Village, Jombang District, Jombang Regency, using purposive sampling from February to June 2021. The number of samples in this study amounted to 96 respondents. This study shows 1) the form of utilization of yardland conducted by the community is covering agriculture/plantations, farms, and other business entities 2) The amount of capital used in the utilization of yardland starting from Rp. 500.000,. – Rp. 1.500.000,. 3) The utilization of yardland contributes to improving the household economy and daily needs.